Resistence in times of crisis. The complicit (contaminated and contaminating) gaze of the researcher - Reyes, Román (Nómadas. Critical Journal of Social and Juridical Science, 2017)
The gaze (that of the researcher that looks), if it assumes its status as an agent that legitimizes itself in its profession, if it innovates, while being responsible for the will to progress that it makes explicit, involves: a) reaffirming the alleged historical and social determination of knowledge; b) admitting that theoria (praxis) is a prosthesis; and c) that it is possible to touch without con-tacting, that is, trans-forming.
Keywords: complicit gaze; apologies; pre-texts; complicity; innovation